(untitled) (Chittagong University Journal of Biological Sciences, 2024)
Analysis of nests of ten species of passerine birds from the collection of the Bangabandhu Jamuna Multipurpose Bridge Regional Museum, Tangail, Bangladesh was conducted during February to April 2010. In total 77 nests of the species studied were measured from outer surface of the sealed glass-boxes and the nest materials were identified. The nesting plants and nesting heights were analyzed from the records of the museum. The Chittagong Univ. J. B. Sci.,Vol. 7(1 &2):45-57 , 2012.